Review of "Public Law in Nahj al-Balaghah" - Hussein Javan Arasteh (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The publication of the book "Public Law in Nahj al-Balaghah" is admirable in terms of the supreme position of Nahj al-Balaghah in religious culture as well as in terms of the status of public law in comparison with other branches of law. The method of evaluation of this book is citation-analytical, and it is in accordance with the proposed model of the review committee for the Study of Texts and Books of the Humanities in the framework of general introduction, and review of the form and content of the book.The book's strengths in terms of content include Islamic approach to public law, extensive reflection on Nahj al-Balaghah, and proper matching of titles with selective samples in most cases; however, this book suffers from logical disorder and content cohesion, inaccuracy and incompleteness. In some cases, the author's perceptions of Imam Ali impressions in Nahj al-Balāghah can be criticized.In spite of the great importance of constitutional law as the most important branch of public law, a large number of issues relating to sovereignty and government, governmental institutions and the rights of the nation, which are subdivided are the smallest number of pages is devoted to it, and it is underestimated.The technical quality of the book is good, and the general rules of writing are respected; however, weaknesses in book form include lack of proper organization of the book, the proportions of the length of the chapters and the exhaustion of the annexed book.